DAMPAK E-COMMERCE TERHADAP PENGENDALIAN INTERNAL DAN PROSES AUDIT - SHIELDSA WIJONO, VIRTANIA (: 2303-1719)
The usage of an Internet has been developing fastly in recent years. Many companies have been increased their business competitiveness by following these developments to make cooperation and doing trade electronically, which is popularly known as e-commerce. E-commerce is defined as the ability to conduct transactions between two or more parties using computers which is connected together in networks. E-commerce on the entire transaction is conducted electronically and some corporate accounting system can be accessed by outsiders, it brings an impact for its internal control. E-commerce brings an impact for company internal control that raises new issues regarding the validity of transactions, transaction authorization, and security of company property. On e-commerce business the need of physical evidence in the form of paper will also be decreased because all the electronic documents, electronic data, electronic payments, digital signatures and electronic transactions, it saves more paper in the company environment, also known as paperless. Those changes also impact in company auditing process which is did by an external auditor because all of the evidences are in electronical proof. So external auditor has to understand the company’s accounting internal controls system to obtain reliable evidence. As a note to get an evidence, analysis evidence and to test internal control and substantive, the external auditor is required to use a software audit.